Synthesis of Biodiesel from Panaga Oil - Muhammad Ibrahim bin Sa'dan, Muhammad Ibrahim (Universiti Teknologi Petronas, 2009)
Biodiesel refers to a non"petroleum-based diesel fuel consisting of long chain alkyl esters, made by transesterification of vegetable oil or animal fats, which can be used in unmodified diesel-engine vehicles. Basically, biodiesel is originated because of depleting in earth crude oil sources and environmental concern. So, biodiesel can be considered as renewable replacement for petroleum-based diesel engine fuel. In the study, the main objective is to synthesis biodiesel where the biodiesel will be extracted from Penaga oil through in-situ method; reaction mjxture of penaga oil and alcohol using acid-catalyst to produce biodiesel. Some parameters such as reaction temperature, catalyst concentration and particle sizes are manipulated to observe the effects and get the desired product with optimize condition. Literature review section discussed about Penaga plant background, biodiesel production through conventional method and in-situ method of transesterification, effects of each parameter; reaction temperature, catalyst concentration and particle size respectively. Design of experiment being used is Taguchi Method; L9 Array as it is provides uniformly distributed coverage of the test domain, concise test set with fewer test cases is created, all pair-wise combinations of test set created, simpler to generate and less error prone than test sets created manually and reduces testing cycle time. Basically, the project jobs scope will be carried out are: 1) Penaga Seed Preparation; 2) Oil extraction; 3) Acid Value; 4) In-situ Transesterification and 5) TLC Qualitative Analysis. As conclusion, it is believed that this method is feasible and Penaga could be commercialized as biodiesel feedstock considering the optimum conditions for the variables and parameters used.